Barriers to nurse-led delirium management in intensive care units: an integrative systematic review using COM-B model - Mokhtar Abdu Almoliky; Sameer Alkubati; Khalil Saleh; Salman Alsaqri; Saddam A. Al-Ahdal; Galal Albani; Mujeeb A. Sultan (BMC Nursing)
Abstract Background Development of effective guideline for delirium management is still seeking nowadays. As nurses are in the first confrontation line for delirium, their prospective in identifying barriers are essential in developing integrated strategies and clinical guidelines. Objective To explore the barriers focusing on intensive care unit (ICU) nurses’ point of views to provide an evidence-based support for effective nurse-led delirium management in ICU settings. Methods Whittemore and Knafl framework was recruited to build up this integrative review. PRISMA guidelines were followed to search about barriers of nurse-led delirium management. Articles published up to June 2024 in five databases; Web of Science, Scopus, PubMed, CINAHL and EMBASE using related keywords were involved. Mixed Methods Appraisal Tool (MMAT) was used to evaluate the quality of articles included in this review and then reported nurse-led delirium barriers were mapped according to COM-B model. Results Twenty-three articles out of 1,020 research articles were included in this review after carefully checked according to the exclusion and inclusion criteria. based on MMAT, 7 articles achieved 100%, 11 articles were achieved 80%, and 5 articles achieved 60%. Nurses’ knowledge deficit is the most common psychological capability barriers of nurse-led delirium management, while complexity of delirium screening tools was found to be a physical capability barriers. High workload, lack of staff, lack of time, lack of documentation and lack/ shortage of guidelines were barriers mapped to physical opportunity, while communication barriers in particular patient’s intubation and sedation were mapped to social opportunity barriers. Motivation was represented by addressing delirium as a major problem, self-confidence, psychological support and considering nurse’s views. Conclusions Nurse’s knowledge deficit, complexity of delirium screening tools, high workload, lack of time, lack of documentation, lack/ shortage of guideline, and impaired communication were barriers of nurse led delirium management. This study is promising in ease of application in clinical practice since delirium barriers in ICU settings were well-presented in a COM-B framework that may facilitate therapeutic strategies and related decision making.